Pessimism Towards Gender Deconstruction in X: A Fabulous Child’s Story by Louis Gould - Paramita Ayuningtyas (Humaniora, 2014)
Research focuses on Lois Gould’s complex position in feminism movements as displayed by the pessimistic tone in one of her works. The primary data for this research were taken from the short story X: A Fabulous Child’s Story, published in 1972. The research used qualitative method that lies on library research, and to help analyze the topic, books, websites, and scientific journals were used. Kate Millet’s concept of an androgyny was also applied in order to study further about the character of X. The result of the discussion shows that even though considered progressive for its era for its effort to deconstruct rigid gender divisions, this short story also comes with an irony with its ending. The ending demonstrates that human beings cannot be free from sex and gender barriers. This result supports the idea that Gould is trapped between the feminist and the antifeminist movement.